Pathophysiological association of expression hormone of adipose tissue omentin-1 and the degree of vascular remodeling of brachyocephalic vessels in persons with obesity and disorders of carbohydrate metabolism - Kulynych, Roman Leonidovich; Soloviuk, Olena Anatolyevna; Soloviuk, Oleksandr Olegovich (Journal of Education, Health and Sport, 2020)
Introduction. The relationship of visceral obesity and excess body weight (EBW) with the development of cardiovascular diseases, type 2 diabetes mellitus (DM) and effect on quality and duration of life determine the relevance of studying this problem. Objective: to assess omentin-1 metabolism and pathophysiological relationship between its level and the severity of lesions in the intima-media thickness (IMT) of the carotid arteries in type 2 DM in combination with EBW and obesity. Material and research methods. We examined 98 people with DM, the first group consisted of 64 people with EBW and obesity, second group consisted of 34 people with normal body weight, control group – 28 healthy individuals. Research results. Evaluation of the correlation matrix showed the presence of a positive rather strong negative connection between IMT, especially the right carotid artery and the level of omentin-1 in the blood (Rs = –0.55; p = 0.002). According to the results of the regression analysis and the study of the scatter diagram of the obtained data, the functional relationship between IMTright / IMTleft and the serum omentin-1 indicator was reliably approximated by a step-type model (polynomial curve, R = 0.49, R2 = 0.24, normalized R2 = 0.22 at F = 10.59, standard error 0.15, p <0.01)). The columnar bivariate 3D histogram clearly shows the physiological relationship between these indicators and indicates that the largest number of individuals with omentin-1 levels from 5-10 ng / ml had significant disorders of the vascular wall (IMT from 1.0 to 1.2 mm). Conclusion. Obtained data indicate a statistically significant associative relationship between the dynamics of the predictor of cardiovascular risk – IMT with the degree of impaired expression of omentin-1.